Shadow - Oakes, Colleen (Oakes, Colleen. Wendy Darling, 2017)
"War has come to paradise, and the Neverland you know will never be the same. Wendy Darling finds herself once again in the arms of Peter Pan, a charming god-child who desires power above all things. Instead of the passion she once had for him, however, this time Wendy's heart burns with a secret: with Hook as her ally, she is there to defeat the evil that lies inside of Peter, the darkness that holds all Neverland hostage--the Shadow. This is a task made nearly impossible by the arrival of Booth, her sweetheart from London and a new pawn in Peter's manipulative game--a boy whose heart she must break in order to save his life. As all of Neverland prepares to fight, Wendy races to untangle Peter's connection to the Shadow, a secret long buried in the Forsaken Garden. When the time comes, all of Neverland will rise to fight--but if Wendy can't call the Shadow, everything she is fighting for will be destroyed. Is Wendy's love for her family enough to save them, or will Peter's madness consume them all?"--Back cover